2015
DOI: 10.1155/2015/151740
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Force Microscopy Study of Zr2Co11‐Based Nanocrystalline Materials: Effect of Mo Addition

Abstract: The addition of Molybdenum was used to modify the nanostructure and enhance coercivity of rare-earth-free Zr2Co11-based nanocrystalline permanent magnets. The effect of Mo addition on magnetic domain structures of melt spun nanocrystalline Zr16Co84-xMox(x=0, 0.5, 1, 1.5, and 2.0) ribbons has been investigated. It was found that magnetic properties and local domain structures are strongly influenced by Mo doping. The coercivity of the samples increases with the increase in Mo content (x≤1.5). The maximum energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The difference in phase angle between free and interacting cantilever oscillation causes a phase shift that increases with increasing bilayers. The larger the phase shift, the better the magnetic properties of the samples [50]. A negative phase shift over small magnetic domains was observed in MFM images.…”
Section: Quantitative Analysis Of Topography Of Combinatorialmentioning
confidence: 84%
“…The difference in phase angle between free and interacting cantilever oscillation causes a phase shift that increases with increasing bilayers. The larger the phase shift, the better the magnetic properties of the samples [50]. A negative phase shift over small magnetic domains was observed in MFM images.…”
Section: Quantitative Analysis Of Topography Of Combinatorialmentioning
confidence: 84%
“…The hemolysis assay was performed using the method reported in the literature. 9 Briefly, 3 ml of blood was collected in EDTA vials. The blood was centrifuged at 6000 rpm for 10 minutes to separate blood cells from plasma, blood cells (RBCs) were washed 5 times with isotonic PBS.…”
Section: Methodsmentioning
confidence: 99%
“… 8 Many studies reported the incorporation of hydrophilic iron oxide nanoparticles (IONPs) in the aqueous core of liposomes but only a few research groups showed interest in developing magnetic microbubbles by integrating hydrophobic IONPs in the lipid bilayer for use as negative T2 contrast agent in MRI. 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation